The Influence of Social Support Factors on Performance: A Case Study of Elementary School Teachers - Novitasari, Dewiana; Asbari, Masduki; Purwanto, Agus; Fahmalatif, Farida; Sudargini, Yuli; Hidayati, Laily Hidayati; Wiratama, Jansen (IJOSMAS, 2021)
This study aims to measure the effect of social support (supervisor, peer, and family support) on teacher performance in five private elementary schools in Tangerang. Data collection was carried out by simple random sampling to 102 primary school teacher populations. The results of the questionnaire were valid and returned as many as 92 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study concluded that all social support factors consisting of supervisor support, peer support, and family support had a positive and significant effect on performance. While the support supervisor has no significant effect on the performance of elementary school teachers. This new research proposes a model for building performance among private primary school teachers in Tangerang through increasing social support for teacher employment.